PERSEPSI SISWA CIBI TERHADAP FAKTOR LINGKUNGAN SEKOLAH YANG MEMPENGARUHI PRESTASI BELAJAR DI SMA NEGERI 1 PADANG - LILY SRIKANDI (Jurnal Penelitian Pendidikan Khusus, 2015)
Lily Srikandi. 2015. “CIBI student’s Perception in Environmental Factors   Affecting School Achievement in SMA 1 Padang”.                             The background of this research based on Perspective society to the best schools in the city of Padang, one of them is SMA 1 Padang. There are some CIBI ( Cerdas Istimewa Bakat Istimewa) students but even more emphasized by researcher are children with high intelligence or special smart . CIBI Student achievement in learning is not in doubt. They were given the nickname of CIBI Students based on the results of learning and achievement that they have acquired. Researcher was interested to examine the perceptions of students CIBI student these to environmental factors that influence learning achievement. Researchers want to know whether the school environment also influence academic achievement.               The methodology of this research is descriptive with quantitative approach. The sampling technique is totally sampling with the number of respondents as many as 24 CIBI students in SMA 1 Padang. Data collection through a questionnaire using a Likert scale with alternative answers yes, hesitantly and no, and there are 43 items that relate to the perception students CIBI against external factors that affect the school environment learning achievement . The collected data were analyzed using statistical formulas percentage.               Based on the results of these studies are 81.49 % of students answered "yes ", 17.08 % of students answered “hesitantly”, and 1.45 % of students answered “no”. It can be concluded that the perception CIBI Student of the environmental factors that influence school learning achievement is very good. So, It  means that the school environment factors provide very good influence on learning achievement CIBI Student at SMAN 1 Padang .Key word: school environment, CIBI student’s, perception